Identification of Paddy Stages from Images using Deep Learning - Himanshushekhar Chaurasia; Alka Arora; Dhandapani Raju; Sudeep Marwaha; Viswanathan Chinnusamy; Rajni Jain; Mrinmoy Ray; Rabi Narayan Sahoo (Journal of the Indian Society of Agricultural Statistics, 2025)
Rice, a crucial global staple, is integral to food security. Precise identification of paddy growth stages, booting, heading, anthesis, grain filling, and grain maturity is vital for agricultural decisions. However, a gap exists in recognizing these stages using red-green-blue (RGB) images. This study uses state-of-the-art computer vision and deep learning classification (Convolutional Neural Networks) algorithms to address this gap. Among the studied algorithms, EfficientNet_B0 achieved an impressive 82.8% overall accuracy. Notably, increasing image size from 64X64 pixels to 128X128 pixels significantly enhanced accuracy. A detailed assessment of growth stages revealed varying accuracy levels, with boot leaf being the most accurately detected (95.1%) and anthesis being the most challenging (72.28%). This work significantly advances automated monitoring, empowering researchers in real-time decision-making.